Diversity in smallholder citrus orchards and cultivation bottlenecks: research avenues for improved production in Benin, West Africa - Akohoue, Félicien; SEGNON, ALCADE C.; Achigan-Dako, Enoch Gbenato (My University, 2017)
Despite tremendous efforts made in agricultural sectors in sub-Saharan Africa in the last two decades, fruits production and consumption to reduce malnutrition and chronic diseases remain low and have received less attention. Moreover, our knowledge of the current production situation and options for improvement are still limited. In this study, we investigated citrus farming systems and production bottlenecks to identify leverage points for intensiﬁcation of smallholder citrus farming systems in Benin. We provided a typology of citrus orchards based on 17 quantitative and qualitative variables using Factor Analysis of Mixed Data combined with Hierarchical Cluster Analysis. The typology revealed four categories of citrus farms based on biophysical resources, socioeconomic resources and system management practices. Categories 1 and 2 included farms characterised by less diversiﬁed cropping systems with non-recommended management practices. Orchard categories 3 and 4 included farms with high varietal diversity and improved management practices. However, farmers of category 4 neglected staking and digging practices. The inadequate farming practices explained some of the production bottlenecks, which were orchard-type dependent. We discussed the implications of our ﬁndings and suggested a number of policy and strategic decisions as well as research and development actions for improving citrus production in Benin.